Assessing the impact of stigma reduction interventions in Iran: A qualitative study from the perspective of mental health stakeholders - Hajebi, Ahmad; Hashemian, Seyed Sepehr; Abolhassani, Moussa; Hajebi, Amirali; Alizadeh, Kamyab; Rahnejat, Amir Mohsen; Khademi, Mojgan; Taghva, Arsia (Frontiers in Public Health, 2022)
Introduction: The fear and embarrassment associated with stigmas discourage patients from help seeking behavior, which may explain why even the patients’ loved ones advise them to discontinue treatment to avoid being labeled. In addition, stigmas can lead to personal and family issues, causing patients to disregard their illness. As such, their disease may develop into a chronic condition. This being said, the present study aims to investigate the challenges, solutions, and successes associated with stigmatization in Iran from the perspective of mental health stakeholders. Method: A qualitative study was conducted in the summer of 2022. Purposive sampling was utilized to recruit participants. The primary data collection method involved a focus group interview that lasted 110 minutes. The project manager monitored the interviews, and all research team members attended the meetings, took notes, and made the necessary preparations. After explaining the study’s purpose and ensuring the data’s confidentiality, the interviewer led a focus group discussion. The interviews were recorded with the participants’ consent. A focus group was used to conduct interviews with thirteen individuals until data saturation was reached. Findings: Ten psychologists, psychiatrists, and managers responsible for mental health, two patients, and one patient’s family member participated in the current study as eligible participants. Repeated readings led to the emergence of three main classes under the headings of challenges, solutions, and successes of stigma management in Iran, each containing subclasses. Conclusion: The majority of the proposed solutions in this study centered on raising awareness and training diverse individuals and groups to lessen stigmas. The most crucial de-stigmatization measure is to offer training that will cause the current stereotypes to change. This must be taken by patients and their families as well as therapists, leaders, policymakers, the general public, and the media. Ideally, younger members of the target groups should be considered for these pieces of training, which must be based on research and derived from cultural and localized needs.